Prawne i ekonomiczne aspekty polskiej branży funeralnej – spojrzenie antropologa - Kubiak, Anna E. (1962– ) (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2015)
The main problems I outline are funeral industry legal and economical issues. They concentrate around the following topics: challenges of new technologies, advanced funeral planning, funeral insurance, forms of legitimizing funeral houses, consequences of a criminal case, the so called ‘skin’s affair’ in Łódź, economical problems of funeral market and the problem of funeral advertising. Present Polish law on cemeteries and the legal mandate of the dead comes from the 1959 and duplicates the provisions enacted even earlier, in 1932. The legislation takes into account primarily the Catholic burial regulations, neglecting the other religions, secular funerals and alternative forms of disposal. A new law would enable an evolution of funerals, consistent with ensuring respect for the family, the body of the deceased, individualistic approach to the last rite of passage and could eliminate the pathology at the funeral market. There are no regulations against hiring a mortuary in hospitals if the funeral business is conducted elsewhere. Mutual benefits mean that, in practice, some funeral companies still supply the clinics ‘ budgets. There are still aftermath of the criminal affair called skin’s hunters’: companies continue to pay for the information of the dead received from ambulance staff and hospitals. Still there are investigations concerning violations of professional secrecy by hospital’s personnel and the families of the dead are presented business cards. Staff at the hospitals still passes the companies information about deaths, and this is the place where most of them come. The very advertising in the close vicinity of the hospital is morally questionable. New, modern legal funeral act is very important for professionalization of funeral homes and social status of funeral workers. Polish undertakers from 20 years work on the prestige of the profession
Keywords: funeral industry; legal issues; funeral market; challenges of new technologies